The Experiences of Feedback Practices on Academic Writing Undergone by Students with English as an Additional Language in a Master’s Programme: A Multiple Case Study - Poverjuc, Oxana (Journal of Academic Writing, 2011)
This article reflects upon the experiences and perceptions of feedback practices that five students who spoke English as an additional language (EAL) engaged with as part of their one-year taught master's course at a major UK University. During writing processes and after the submission of assignments, participants received support in a wide range of modes: tutors’ oral, written, and electronic feedback and peer feedback. The paper outlines the key difficulties students encountered when engaging with and responding to feedback. Findings suggested that although students expressed satisfaction with feedback practices provided over the course of their master's degree, instances in which these events constrained their understanding of writing conventions have been documented. Such factors as appropriate timing, the nature of feedback, the type of language tutors employed when providing feedback, variation in tutors’ preferences for marking, as well as students’ individual and cultural differences, sometimes limited students’ understanding and use of feedback.